HE GENERA BELOTIA Rich. AND TRICHOSPERMUM Bl. (Tiliaceae) - AJGH Kostermans (BRIN Publishing (Penerbit BRIN), 1962)
The genus Belotia was founded in 1845 by A. Richard (in R. de la liagra, Hist. Cuba, Bot. 1: 207), based on a single species: B. grewiifolia; liichard added Grewia mexicana DC. (1824) as a synonym.Sprague (in Kew Bull. 1921: 270-278) wrote a monograph on the knus. He characterized Belotia as follows: Presence of nectaries at the Itase of the petals and their absence on the androgynophore; the blue or Inlet, rarely white petals, the bilocular ovary with pluriovulate loculi; the a– culicidal capsule, strongly compressed transversally to the septum and a–ediscoid ciliate seeds. He than adds: